(untitled) (Veterinary Science, 2017)
The aim of this study was to evaluate a possible myocardial damage on feedlot steers caused by high doses of monensin (MN). A commercial kit was used to determinate the concentration of myocardial creatine kinase (CK-MB). Four groups of animals were conformed according to the diet MN concentration. G1: Control, without MN, G2: MN Tag dose, 1 mg kg body weight (BW) -1 , G3: MN 5 mg kg BW -1 and G4: MN 10 mg kg BW -1 The cattle were housed in pens for eleven days. Venous blood samples were taken at 0, 48, 120, 168 and 264 h. Serum CK-MB concentration was analyzed using descriptive and comparative statistics analysis of variance (ANOVA) with a significance level of P<0,05. No CK-MB mean concentration above cut-off level (90 U/l) was recorded throughout the assay for any treatment. The G1 mean throughout the assay was 47,84 ± 21,28 U/l showing statistical differences (P<0.05) from 120 h up to the end of the study, as compared to the others groups. Means of G2, G3 and G4 were 37,31 ± 37,31; 34,09 ± 12,96; 34,62 ± 19,90 U/l, respect tively. This study could not determine heart damage caused by MN, measured through a commercial kit, despite the widespread time assessed. The control group had higher CK-MB mean concentration than all others groups, from 48 h until the end of the study. This result could indicate a possible beneficial and regulatory effect on digestive microflora by the MN antibiotic, resulting in less exposure to bacterial endotoxins